IMPLEMENTATION OF ISLAMIC BUSINESS ETHICS IN ONLINE BUYING AND SELLING BUSINESS - Lutfi Riadi; Sunardi Sunardi (IJED: International Journal of Economy Development Research, 2022)
The main problem of this research is how online buying and selling actors apply business ethics in buying and selling transactions at Shopee.com. The sources for this research are 2 sellers at Shopee.com who have a store rating of 4.7 stars. While the sources as buyers are 2 people who make purchases at Shopee.com more than 2 times a month. The data used in this research is primary data collected through interviews and observations. Data analysis used qualitative data analysis. The results of the study show that the application of business ethics in Shopee.com is in line with Islamic business ethics. The implications of this research provide input in efforts to improve the application of business ethics.